Testing Moral Disengagement and Proteus Effect Predictions on Feelings of Guilt and Self-Empowerment Attributed to Bearing Guns - Huang-Isherwood, Ke M.; Peña, Jorge (Frontiers in Psychology, 2021)
This study (179 participants, mean age 19.98, 85% female) examined how violence justification via avatar role manipulations affected first-person shooter game players’ subsequent feelings of guilt and self-empowerment attributed to bearing guns in the real-world. In support of the moral disengagement in violent video games model, an independent samples t test suggested that participants assigned to play as gang members shooting at police officers felt guiltier than those assigned to play as police officers shooting at gang members. In support of Proteus effect predictions linked with self-perception and priming mechanisms, a one-way repeated measures analysis of variance suggested that self-empowerment attributed to carrying guns for both avatar roles increased from baseline to after gameplay, but avatar roles did not influence the increase. The lack of influence could be because participants did not adopt avatar behaviors with undesirable connotations. The results highlight avatar-user bonds through which the associations raised by virtual personas affected players’ emotions and self-perception when engaging in simulated violence.